The effect of canakinumab on COVID19-associated cardiomyocyte contractile dysfunction and arrhythmias. (14th October 2021) - Dimai, S; Semmler, L; Stachelscheid, H; Pieske, B M; Heinzel, F R; Hohendanner, F
Abstract: Background: Cardiac injury associated with cytokine release occurs in almost 20% of SARS-CoV-2 positive patients during hospitalization and mortality is particularly high in these patients. Cardiac enzyme (e.g. troponin or creatinine kinase (CK)) elevations are a frequently reported finding, indicating myocardial damage and arrhythmias are the cause for ICU transfer in up to 12% of patients. However, the mechanistic role of COVID19 associated cytokine-storm for the concomitant cardiac dysfunction and associated arrhythmias is unclear. In addition, the role of anti-inflammatory therapy approaches to mitigate this cardiac dysfunction remains elusive. Methods: We investigated the effects of COVID19-associated inflammatory response on cardiac cellular function as well as its cardiac arrhythmogenic potential in rat and induced pluripotent stem cell derived cardiomyocytes (iPSc-CM). Moreover, we evaluated the therapeutic potential of the IL1-beta antagonist Canakinumab using state of the art in-vitro confocal and ratiometric high-throughput microscopy. Results: Isolated rat ventricular cardiomyocytes were exposed to control or COVID19 plasma from intensive care unit patients with severe ARDS and impaired cardiac function (LVEF 41±5%; 1/3 of patients on veno-venous extracorporeal membrane oxygenation; CK 154±43 U/l). Cardiomyocytes showed decreased Ca2+ transient amplitudes and altered baseline Ca2+ concentrations leading to impaired cellular contractile function upon electrical field-stimulation and exposure to patient plasma (n=276 control and 359 COVID19 cells; Fura). In addition, we used iPSc-CM to explore the long-term effect of patient plasma on cardiac electrical and mechanical function in a translational setting (24h incubation; Fluo). In iPSc, spontaneous Ca2+ release events (i.e. Ca2+ waves and Ca2+ sparks) were more likely to occur upon incubation with COVID19 plasma and nuclear as well as cytosolic Ca2+ release were altered. Co-incubation with Canakinumab had no effect on pro-arrhythmogenic Ca2+ release or Ca2+ signaling during excitation-contraction coupling but influenced cellular automaticity upon prolonged electrical stimulation. Conclusion: Plasma derived from COVID19 patients exerts acute cardio-depressant and chronic pro-arrhythmogenic effects in rat and iPS-derived cardiomyocytes. Chronic co-incubation with Canakinumab had no beneficial effect on cellular Ca2+ signaling during excitation-contraction coupling. Funding Acknowledgement: Type of funding sources: None.